Supervised Machine Learning Algorithm to Classify Gender in Google Colaboratory - J., Praveen Gujjar; V., Naveen Kumar (Indian Journal of Computer Science, 2021)
Supervised machine learning uses the label dataset to classify data. In this paper supervised machine learning algorithm Random Forest Classifier and Support Vector Machine learning algorithm are used to classify gender. Google Colaboratory is a Cloud based service which is also known as Colab. Google Colab is based on Jupyter Notebook where machine learning and deep learning concepts can be implemented. Google Colab provides free access to GPU which is very much required to disseminate Random Forest and Support Vector Machine Learning concepts. This paper made an attempt to classify gender based on the person’s height, weight, and shoe size using Random Forest and Support Vector Machine. The result shows that Random Forest Classifier accuracy is relatively better when compared with Support Vector Machine learning algorithm.